Calitatea mediului participativ - Costin, Cornelia (Calitatea Vieții, 1991)
The central problem of this article is the link between the political participation and the quality of life. I mean, the endeavour to find and answer to the question: is the man able to influence the quality of his own life through his participation in policy – “supervising” and, if need be, “punishing” – through his dialogue with the power? And, if the answer is “yes”, the new questions: how? and whither? The answer cannot be considered in an absolute way, being “open” to a lot of different points of view and interpretations. But this is my opinion: taking part in the political life, man can be able to score steps forward in finding out the inner equilibrium, the “happiness”, a concept which lies at the basis of the “quality of life” one.